2011
DOI: 10.4161/mabs.3.4.16092
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin A

Abstract: Although immunoglobulin (Ig) A is commonly recognized as the most prevalent antibody subclass at mucosal sites with an important role in mucosal defense, its potential as a therapeutic monoclonal antibody is less well known. However, IgA has multifaceted anti-, non-, and pro-inflammatory functions that can be exploited for different immunotherapeutical strategies, which will be the focus of this review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 138 publications
0
51
0
Order By: Relevance
“…A number of studies have reported that the IgA Ab may have more advantages than IgG antibodies for inhibiting tumor growth and infectious diseases via mediation of immune cell targeting (40). For example, IgA antibodies are far more effective than IgG anti-tumor antibodies in recruiting neutrophils for destruction of lymphoma and solid tumor targets (4143).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported that the IgA Ab may have more advantages than IgG antibodies for inhibiting tumor growth and infectious diseases via mediation of immune cell targeting (40). For example, IgA antibodies are far more effective than IgG anti-tumor antibodies in recruiting neutrophils for destruction of lymphoma and solid tumor targets (4143).…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic antibody field is currently dominated by IgG-based mAbs. The advantages of opening up this arena to include IgA-based mAbs are becoming increasingly apparent, piquing interest in both academia and industry [79,[131][132][133]. One advantage is the new prospects it offers in terms of intellectual property, in what is already a complex landscape [134].…”
Section: Advantages Of Iga-based Therapeuticsmentioning
confidence: 99%
“…Antibody-dependent enhancement of viral infections are major hurdles in the development of effective vaccines. This enhancement is likely facilitated by the Fc domain of IgG but not for its isotype variant IgA 18 . The avidity of mucosal IgA, in comparison with IgG, due to the multimeric structure, enhances the antibody binding with antigens.…”
Section: Introductionmentioning
confidence: 99%